Dynamic balance test modifications in Karate Kata: Content validity - S, Wedi; Gemaini, Andri; Fauzi, Fauzi; Prabowo, Trisnar Adi (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The aim of this study was to test the content validity of the modified Karate Kata dynamic balance test. This research employed a mixed-methods approach. The first stage involved analyzing journal documents, while the second stage focused on validating the dynamic balance test construction through expert judgment, using the Delphi technique with 10 experts. In the final stage, a qualitative analysis was carried out consisting of suggestions from expert judgment. The instrument consists of a questionnaire with a 1–4 rating scale. Data were analyzed using Aiken’s V. In the first stage, the results showed differences among the tests used to measure athletes’ dynamic balance abilities. Based on these findings, the dynamic balance test was modified. In the second stage, the analysis of the first test item revealed a coefficient value of 0.825 (high). The second item, which assessed conformity with the characteristics of Karate Kata movements, had a coefficient value of 0.792 (moderate). The third item, evaluating the dynamic balance test procedure, had a coefficient value of 0.819 (high). The Karate Kata dynamic balance test demonstrated high content validity (coefficient = 0.812), with all experts agreeing on the modifications. The test is now more specific and better aligned with Karate Kata movement characteristics.